2018
DOI: 10.1002/slct.201803202
|View full text |Cite
|
Sign up to set email alerts
|

TGA, DSC and DFT Studies of TKX‐50, ABTOX and Their Key Precursors

Abstract: TKX‐50 (Dihydroxylammonium 5,5’‐bistetrazolate‐1,1’‐dioxide) and ABTOX (Diammonium salt of 5,5’‐bistetrazole‐1,1′‐diolate) being simple and cheap to prepare from commonly available chemicals, are emerging as promising energetic materials along with the advantages like required thermal insensitivity, low toxicity and safe handling. In order to synthesize such powerful materials with utmost care, it is essential to know about the precursors and reaction intermediates involved. Therefore, the detailed thermal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The NASA SP‐273 computer code was used to predict the parameters of rocket propellant formulations, and was able to show that TKX‐50 containing formulations showed a superior specific impulse value compared to corresponding formulations in which TKX‐50 was replaced by other common explosives [14] . Based on this work, the authors concluded that the theoretically predicted data indicated that TKX‐50 has potential for application in rocket and gun propellants [14] …”
Section: High‐energy Explosive Component Hmx Cl‐20 Tkx‐50mentioning
confidence: 92%
See 2 more Smart Citations
“…The NASA SP‐273 computer code was used to predict the parameters of rocket propellant formulations, and was able to show that TKX‐50 containing formulations showed a superior specific impulse value compared to corresponding formulations in which TKX‐50 was replaced by other common explosives [14] . Based on this work, the authors concluded that the theoretically predicted data indicated that TKX‐50 has potential for application in rocket and gun propellants [14] …”
Section: High‐energy Explosive Component Hmx Cl‐20 Tkx‐50mentioning
confidence: 92%
“…[14] Based on this work, the authors concluded that the theoretically predicted data indicated that TKX-50 has potential for application in rocket and gun propellants. [14] The properties of composite propellants containing TKX-50 have been investigated experimentally with different mass fractions of TKX-50 particles -specifically on TKX-50/HTPB binder slurries and AP/HTPB/Al propellant slurries. [15] It is possible with the inclusion of specially selected energetic materials to increase the gravimetric specific impulse or the density specific impulse of propellants, however, the energetic materials chosen for this purpose must show low sensitivity to external stimuli such as impact and friction.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, improving the stability of HEDMs and reducing its sensitivity is the main focus of current research in the field of materials science [5, 6]. Recently,studies have found that when the crystal structure of the compound is coplanar, it is beneficial to achieve a fine balance between the high‐energy properties and stability of HEDMs [7, 8]. For example, 1,3,5‐triamino‐2,4,6‐trinitrobenzene (TATB) and 3,3′‐diamino‐4,4′‐azofurazan (DAAzF) with coplanar crystal structures have good stability and lower sensitivity [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal hazard assessment of TEX also has been carried out by using accelerating rate calorimeter and the results are reported in literature . There are reports wherein, computational and experimental techniques have been used to determine the thermal behaviour of energetic molecules …”
Section: Introductionmentioning
confidence: 99%